If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 5)(x + -3) = 0 Reorder the terms: (5 + 4x)(x + -3) = 0 Reorder the terms: (5 + 4x)(-3 + x) = 0 Multiply (5 + 4x) * (-3 + x) (5(-3 + x) + 4x * (-3 + x)) = 0 ((-3 * 5 + x * 5) + 4x * (-3 + x)) = 0 ((-15 + 5x) + 4x * (-3 + x)) = 0 (-15 + 5x + (-3 * 4x + x * 4x)) = 0 (-15 + 5x + (-12x + 4x2)) = 0 Combine like terms: 5x + -12x = -7x (-15 + -7x + 4x2) = 0 Solving -15 + -7x + 4x2 = 0 Solving for variable 'x'. Factor a trinomial. (-5 + -4x)(3 + -1x) = 0Subproblem 1
Set the factor '(-5 + -4x)' equal to zero and attempt to solve: Simplifying -5 + -4x = 0 Solving -5 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -4x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -4x = 0 + 5 -4x = 0 + 5 Combine like terms: 0 + 5 = 5 -4x = 5 Divide each side by '-4'. x = -1.25 Simplifying x = -1.25Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {-1.25, 3}
| 1/3y-7/2=-7/4 | | 9/12+2/9 | | 52-5x=2 | | 2x+7=-2x+7 | | 9(b-4)-7b=5(3b-10) | | 1/12y=15 | | 8+4b=18 | | 3/7=-4/x+5 | | (-5/c)=(1/3) | | 1/4(20-4x)=6-x | | 12-q=8 | | x+7/3=7 | | (2/7)=(x/-42) | | -4-x=6x-4 | | y-8+6y=-9+5y+1 | | 12=e/12 | | 7x+8=8+6x | | 4x+11=5x+4 | | x+1.35=2 | | -4/7-1/2v=-2/3 | | 3w=4w+-10 | | (7/10)*(4/5) | | 3-4x=2x+21 | | (x/4)=(3/2) | | 44=28-4(x-2) | | 5/14=p/49 | | 5x+10=-100 | | -4x+7=-6x+17 | | E/12=13 | | 20-d=13 | | 15-3y+2=5 | | 4((x^2)-6x+9)=192 |